Treatment of patients with acute and subacute dorsalgia - O. N. Gerasimova; V. A. Parfenov; E. Yu. Kalimeeva (Неврология, нейропсихиатрия, психосоматика, 2018)
Objective: to investigate the efficiency of treatment for acute and subacute dorsalgia, by providing information to patients and by using nonsteroidal anti-inflammatory drugs (NSAIDs) without conducting physical therapy, reflexotherapy, and manual therapy. Patients and methods. A total of 140 patients (87 women and 53 men; mean age 50.7±17.6 years) with acute and subacute back pain were followed up. Out of them 127 (91%) patients were found to have nonspecific (musculoskeletal) pain; 13 (9%) had discogenic radiculopathy. All the patients were informed of the benign nature of the disease, the high probability of its rapid resolution, the feasibility of abandoning prolonged bedrest, and the lack of need for physical therapy, reflexotherapy, massage, and manual therapy. To reduce pain, the patients received meloxicam 15 mg/day orally or intramuscularly or first 15 mg/day intramuscularly and then orally. The investigators assessed pain intensity with the numerical rating scale and functional activity restrictions with the Roland-Morris disability (RMD) questionnaire. Results. After treatment, the visual analogue scale pain intensity scores decreased from an average of 6.4 to 1.0; the RMD scores dropped from 6.8 to 1.4 (p<0.001). The duration of treatment averaged 11.0±4.4 days. Comparison of different meloxicam dosage regimens showed no significant differences; a positive result was noted in all cases. No adverse events were observed during treatment. Conclusion. The investigation has shown the high efficiency of management in patients with acute and subacute dorsalgia, by providing information to patients (an education conversation), by using meloxicam, and by applying a personalized approach (treatment for concomitant diseases and conditions). Refusing physiotherapy, massage, acupuncture, and manual therapy substantially reduces the cost of treatment in patients with acute dorsalgia.